2011
DOI: 10.1177/1524839911404232
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Media Campaign on Fetal Alcohol Spectrum Disorders for Northern Plains American Indian Communities

Abstract: Alcohol-exposed pregnancies are especially of concern for American Indians. The Indian Health Service reported that 47% to 56% of pregnant patients admitted to drinking alcohol during their pregnancy. In addition, rates of Fetal Alcohol Syndrome are estimated to be as high as 3.9 to 9.0 per 1,000 live births among American Indians in the Northern Plains, making prevention of alcohol-exposed pregnancies an important public health effort for this population. The goal of this article is to add to the literature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 16 publications
2
42
0
1
Order By: Relevance
“…The Hanson et al . study [32] used a self‐report measure of knowledge, asking participants to indicate whether the media campaign had increased their knowledge about the effects of alcohol on unborn children.…”
Section: Resultsmentioning
confidence: 99%
“…The Hanson et al . study [32] used a self‐report measure of knowledge, asking participants to indicate whether the media campaign had increased their knowledge about the effects of alcohol on unborn children.…”
Section: Resultsmentioning
confidence: 99%
“…Se realizó una evaluación y se encontró que hubo aumento en el conocimiento y disminución en el consumo de alcohol en el embarazo, es decir, se hizo una contribución positiva en este tipo de comunidades 14 .…”
Section: -147unclassified
“…Most of the included studies found some improvements in knowledge attributed to the public health interventions. Further, two of four studies involving women of fertile age reported decreased alcohol consumption after the interventions (Hanson et al, 2012;Kaskutas & Graves, 1994). The authors of the review concluded that, due to the limited number of studies on public health interventions to reduce alcohol consumption during pregnancy, the evidence of their effectiveness is limited and more research is needed (Crawford-Williams et al, 2015).…”
Section: Prevention Of Alcohol Consumption During Pregnancymentioning
confidence: 99%